Analisis Peluang dan tantangan : studi pada usaha burasa kelurahan Tanamodindi kota palu - Firayani Firayani; Rini nuraeni; Siti nurwahida; Natasya indriyanti Dg.Maralla; Megawati Megawati; Dandan haryono; Suasa Suasa (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study aims to analyze opportunities and challenges: a study on the business of burasa in Tanamodindi village, Palu city. Burasa is one of the typical foods of Sulawesi made from rice processed with coconut milk and banana leaves. The research method used is a qualitative approach using interviews and observations as data collection techniques. The informants of this study consisted of MSME actors in Tanamodindi village. The results of this study show that the existence of burasa can open up job opportunities for local residents, reduce the unemployment rate, and build a more productive, competitive and independent society. However, the results of this study also found factors inhibiting the sale of burasa including limited access to capital, business networks, and fierce competition. This research is expected to provide a better understanding of the analysis of opportunities and challenges: a study on the business of burasa in Tanamodindi village, Palu city.